Bounds on Lorentz Invariance Violation from MAGIC Observation of GRB 190114C - V. A. Acciari; S. Ansoldi; L. A. Antonelli; A. Arbet Engels; D. Baack; A. Babić; B. Banerjee; U. Barres de Almeida; J. A. Barrio; J. Becerra González; W. Bednarek; L. Bellizzi; et al. (AMER PHYSICAL SOC, 2022)
On January 14, 2019, the Major Atmospheric Gamma Imaging Cherenkov telescopes detected GRB 190114C above 0.2 TeV, recording the most energetic photons ever observed from a gamma-ray burst. We use this unique observation to probe an energy dependence of the speed of light in vacuo for photons as predicted by several quantum gravity models. Based on a set of assumptions on the possible intrinsic spectral and temporal evolution, we obtain competitive lower limits on the quadratic leading order of speed of light modification.